A pedometer-based physical activity intervention for patients entering a maintenance cardiac rehabilitation program: a pilot study - Kaminsky, Leonard A.; Jones, Jason; Riggin, Katrina; Strath, Scott J. (Cardiovascular Diagnosis and Therapy, 2013)
Purpose: To compare the effects of an individualized pedometer-driven physical activity (PA) intervention with the usual time-based PA recommendations given to patients entering a maintenance cardiac rehabilitation (CR) program. Methods: A total of 18 subjects entering a maintenance CR program were recruited and completed the study. Subjects were randomized into pedometer feedback [PF: n=10 (2 women), 53.3±8.1 yrs] and usual care [UC: n=8 (2 women), 59.4±9.9 yrs] groups. New Lifestyles NL-1000 pedometers were used to monitor ambulatory PA. Subjects in both groups participated in the same maintenance CR program for a total of 8 weeks and all were encouraged to obtain a minimum of 30-40 min/d of moderate-vigorous-intensity physical activity (MVPA), on days they did not attend CR. Subjects in the PF group were given individualized daily stepcount goals (increase 10% of baseline steps/d each week) for weeks 2-8. Ambulatory PA was measured with pedometers, recording both total number of steps/d and min/d of MVPA. Measures were obtained during the first week of the maintenance CR program and during the 8th week. Data were also compared between days subjects attended and on days they did not attend. Results: By the 8th week of CR, PF subjects increased daily stepcounts by 42% (2,297±1,606 steps/d, P=0.001), with a 36% increase on CR days (2,654±2,089 steps/d, P=0.003) and a 45% increase on days they did not attend CR (1,872±2,026 steps/d, P=0.017). There were no changes observed in the UC group. Conclusions: Providing pedometers with individualized stepcount goals to patients entering a CR program was superior to the usual time-based PA recommendations for increasing PA.